2017
DOI: 10.1002/fsn3.504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods on the nutritional content of three traditional vegetables leaves: Amaranth, black nightshade and jute mallow

Abstract: The study assessed changes in nutritional content of some commonly consumed traditional vegetables subjected to postharvest processes. Amaranth (Amaranthus cruentus L.), black nightshade (Solanum scabrum Mill.) and jute mallow (Corchorus olitorius L.) leaves used as vegetables were subjected to blanching, boiling and drying. The proximate composition and β‐carotene content of fresh and processed leaves were determined. Amaranth, black nightshade and jute mallow leaves had 25.21%, 39.74% and 29.18% of protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 16 publications
9
31
4
1
Order By: Relevance
“…Blanched dried samples showed significantly (p≤0.05) more carbohydrate content than un-blanched dried samples which might be attributed to the breakdown of ketogenic amino acids to glucose during blanching thereby increasing the carbohydrate content of dried green bean samples (Fadupin et al 2014). Similar trend was also reported by Traore et al (2017) in dehydrated amaranth leaves. Also there was a significant (p ≤ 0.05) increase in carbohydrate content with increase in drying temperature.…”
Section: Effect Of Blanching and Drying Temperatures On Physicochemicsupporting
confidence: 90%
“…Blanched dried samples showed significantly (p≤0.05) more carbohydrate content than un-blanched dried samples which might be attributed to the breakdown of ketogenic amino acids to glucose during blanching thereby increasing the carbohydrate content of dried green bean samples (Fadupin et al 2014). Similar trend was also reported by Traore et al (2017) in dehydrated amaranth leaves. Also there was a significant (p ≤ 0.05) increase in carbohydrate content with increase in drying temperature.…”
Section: Effect Of Blanching and Drying Temperatures On Physicochemicsupporting
confidence: 90%
“…Thus most minerals were leached into the boiling water and this led to reduced ash content because the ash contains minerals. These results tally with the work done by Traoré , K., Parkouda, C., Savadogo, A., Ba, F., Regine, H., & Yves, K., (2017) where it was found that the amount of ash reduced after blanching and boiling of vegetables that included jute mallow and Amaranth cruentus L. The authors found that the amount of ash reduced in jute mallow and Amaranth from 12.40% and 16.33% to 9.37% and 14.27% respectively after boiling for 30 minutes due to leaching of minerals in the boiling water.…”
Section: Effects Of Wet Frying and Boiling On Crude Fatssupporting
confidence: 82%
“…Beta-carotene losses due to frying has been attributed to loss of the initial carotenoids concentration because of leaching into oil at higher processing temperature. Traoré et al, 2017 also reported a reduction of beta-carotene in jute mallow and amaranth due to shade drying alone. The results for shade dried samples of jute mallow and amaranth in this study agrees with those reported by Traoré et al, 2017.…”
Section: Effect Of Boiling and Wet Frying On Calcium Contentmentioning
confidence: 93%
See 1 more Smart Citation
“…Les légumes-feuilles améliorent la qualité nutritionnelle des régimes alimentaires en raison de leur composition biochimique et leurs propriétés fonctionnelles [2,3]. Ils constituent une importante source de protéines, de vitamines, de fibres et de minéraux [4,5]. La plupart de ces légumes sont des espèces sauvages des forêts et utilisées par les communautés locales vivant dans différentes zones agroécologiques [6].…”
Section: Introductionunclassified